Perancangan E-Learning Dengan Pendekatan Addie Model (Kasus : Mata Pelajaran Bahasa Inggris – SD Ipeka Tomang) - Siswono Siswono; Yurika Liona (ComTech: Computer, Mathematics and Engineering Applications, 2010)
Problem faced by SD IPEKA Tomang is not reaching its predicted target in English subject. This is caused by less understanding among students in important parts of English which reflected in making sentences or writing essays. Teachers have difficulty in explaining about grammar usage to students, which is the basic knowledge in making sentences. In order to avoid this problem, SD IPEKA Tomang is adding or replacing the teaching media into a computer media. In doing this analysis and designing of e-learning is using ADDIE Model approach. This research is done through stages of analysis, design, and development. Analysis stage uses Gap Analysis approach to understand the needs of e-learning.